Farewell to variables - Valsiner, Jaan (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"This book presents a novel perspective on psychology's methodology-moving it from quantification as a given imperative to science-philosophical look at phenomena-data relationship. The idea for this volume emerged from inquiries into the history of psychology of the 18th-19th centuries where the developmental focus within German Naturphilosophie led philosophers to emphasize the dialectical nature of biological and psychological development. The nature of the natural and social worlds is curvilinear and includes knot-complexes that cannot be investigated in terms of the consensually accepted General Linear Model of the 20th century. In this the new book continues the creative search for new forms of epistemological ways of thinking that was started in 2010 in the volume Methodological thinking in psychology: 60 years gone astray. General Liner Model and turned into metaphoric complexes that acquire life of their own in psychologists' thinking needs to be replaced by qualitative-structural units of thinking about how human psychological organization can be presented"-- Provided by publisher.
Keywords: Psychology -- Methodology.; Psychology -- Research.; Psychology -- Research & Methodology.; Psychological methodology.; elektronické knihy; electronic books